Due Diligence In Order Corporate Action and Transaction Document Creation - Tacia Situmorang, Margaret (Action Research Literate, 2024)
The Indonesian government recently enacted Government Regulation No. 72 of 2016 concerning State Capital Participation and Arrangement in State-Owned Enterprises (BUMN), the Indonesian government argues that the BUMN Holding is necessary for its anticipated positive impacts, such as enhancing company performance through synergy and economies of scale, reducing operational and financial inefficiencies, widespread public concerns exist that the BUMN Holding might lead to unlawful privatization of BUMN, prompting the public to file Judicial Review petitions with the Indonesian Constitutional Court. Hence, this study aims to analyze BUMN Holding based on the BUMN Holding Regulation, Constitutional Law Analysis on the Testing of Government Regulation No. 47 of 2017, and Law No. 19 of 2003 concerning BUMN. The research employs a comprehensive legal analysis approach, scrutinizing the implications of BUMN Holding on constitutional and statutory frameworks. In conclusion, the study sheds light on the potential legal ramifications of BUMN Holding, exploring the delicate balance between government objectives and public concerns surrounding the privatization of state-owned enterprises. The findings aim to contribute to the ongoing discourse on the regulatory landscape of BUMN Holding, providing insights for policymakers, legal practitioners, and the public.